LOGISTICS CONCEPTS AND LOGISTICS 4.0 - Glistau, Elke; Coello Machado, Norge Isaias (Advanced Logistic Systems - Theory and Practice, 2019)
The paper describes the terms Industry 4.0 and Logistics 4.0 as two of the most important trends in production and logistics. Industrie 4.0 (Industry 4.0) is a German term and a synonym for the fourth industrial revolution. It is connected with the common trend of digitalization, virtualization and networking of data and information. The term Logistics 4.0 brands the specific application of Industry 4.0 in the area of logistics. Therefore a new research approach was developed the “Smart Logistics Zone” (SLZ) by Fraunhofer IFF and Otto von Guericke University Magdeburg. This is defined as a scalable examination and action area for the analysis, evaluation, planning, control, regulation and (re-) configuration of logistics solutions [1]. The Smart Logistics Zone differs into logistics objects, logistics processes, logistical systems and logistics infrastructure. Every logistics solution should be built by using all of these four aspects in a free combination by increasing dynamics and complexity. Industry 4.0 and Logistics 4.0 create new business processes. The question is, how will they change the traditional logistics concepts and strategies? The paper answers the following research questions: What are solutions of Logistics 4.0? Are there any successful realized solutions, which optimize logistics at a whole? Which requirements on logistics management will exist according to the criteria of Industry 4.0/Logistics 4.0? Are the classic logistics strategies still valid according to the digital transformation process?